The Structure of Old Norse "Dróttkvætt" Poetry - Gade, Kari Ellen (Book collections on Project MUSE., 1995)
The drottkvett was a form of Old Norse skaldic poetry composed to glorify a chieftain's deeds or to lament his death. Kari Ellen Gade explores the structural peculiarities of ninth- and tenth-century drottkvett poetry and suggests a solution to the...